Investigating the rheological behavior of Witbank coal water mixtures - Owusu Gyebi, Prince (Centre for Minerals Research, 2016)
South Africa has large low-grade coal reserves. With the prospect of expanding its coal demands for exports and power generation, it is important that the beneficiation and transport of coal in the country are economical. The current mode of transporting coal has some drawbacks, which include inefficient rail infrastructure, long distances, and several environmental concerns related to air pollution, water pollution, and traffic risks. It is, therefore, important to investigate efficient means of coal transportation, which will also reduce environmental impacts. The transport of highly concentrated coal-water slurries through pipelines has attracted the attention of many researchers as an efficient and economical means of fine coal utilization. The primary objectives of this study are to investigate the importance of surface charge, solids concentration and particle size on the stability and rheological behaviour of Witbank coal. This work was carried out to arrive at a sounder discernment of the function of dispersion addition on coal-water mixtures rheology and stability.